Halal Certification and Digitalized Halal Supply Chains: A Maqāṣid al Sharīʿah Perspective on Public Policy, Economic Growth, and Welfare - Mohamad Ghozali; Ahmad Hasan Ridwan; Muhammad Hasanuddin (UIN Sunan Gunung Djati Bandung, 2026)
The rapid expansion of the global halal market necessitates robust public policies to ensure ‎product integrity and consumer trust. This study examines halal certification and the ‎digitalization of the halal supply chain from a public policy perspective, employing a ‎conceptual framework grounded in Maqāṣid al Sharīʿah. Using a qualitative descriptive ‎approach with thematic content analysis, the research explores the integration of digital ‎technologies—such as blockchain and artificial intelligence (AI)—within the Sharia Value ‎Chain. The findings indicate that digitalization initiatives, particularly through systems such as ‎SIHALAL, significantly enhance transparency, operational efficiency, and the inclusivity of ‎micro, small, and medium enterprises (MSMEs) by addressing technological disparities through ‎regulatory intervention. Furthermore, embedding Maqāṣid al Sharīʿah principles—specifically ‎ḥifẓ al dīn, ḥifẓ al nafs, and ḥifẓ al māl—into digital supply chain governance functions as a ‎strategic catalyst for sustainable economic growth and social welfare. The study concludes that ‎adaptive public policies emphasizing digital transformation and sharīʿah-by-design principles ‎are essential to mitigating information asymmetry and strengthening national economic ‎resilience.